O que é inovação em mídia e jornalismo?: uma análise de Media Labs e seus projetos - Nunes, Ana Cecília Bisso (2020)
This research stems from the appearance, resurgence and revitalization of media labs around the world (PLOHMAN; BUTCHER, 2010; SALAVERRÍA, 2015; TANAKA, 2011), especially those focused on media and journalism, as a means to investigate media innovation, particularly when related to journalism, in an experimental context. To that end, this thesis addresses the following research problems: what is the context of emergence and the characteristics of media labs focused on media and journalism?; what are the premises of the innovation processes of these labs?; what are the characteristics of the innovation in media and/or journalism in an experimental context through the perception of the leaders of these labs?; and, finally, what are the characteristics of media innovation, particularly when connected to the journalism industry, in an experimental context through these labs? Authors such as Lavine and Wackman (1988), Fergusson (1991), Lindmark et al., (2013), Storsul and Krumsvik (2013) and Dogruel (2013; 2014; 2015) guide this research regarding alreadymapped particularities of media and journalism innovation. The relation with journalism is grounded on authors such as Deuze (2008), Boczkowski (2005), Salaverría (2015), GarcíaAvilés et al., (2019) and Posetti (2018). From a theoretical standpoint, this investigation is based on the building of a media labs database, a survey with lab leaders and a documental analysis of their projects. This research has been conducted in partnership with the World Association of Newspapers and News Publishers (WAN-IFRA), through the Global Alliance for Media Innovation (GAMI), and has identified 123 active labs, mainly in Latin America, North America and Europe. Besides that, 54 media labs leaders from 15 countries answered the survey. As a result, the thesis proposes the emergence of four types of media innovation: (1) Creative Innovation: based on creative-intellectual strategies, exclusively impacting journalistic content/narrative and consumption; (2) Reflective innovation: organizational or process innovation without technological mediation; (3) Exploratory innovation: appropriation of technologies for production, distribution and/or consumption, and (4) Generative innovation: development and implementation of functional innovation for production, distribution and/or consumption. Still, it argues that media innovation, particularly journalistic, demands specific axes of analysis that start from five dimensions: (1) assumptions of innovation, (2) innovative initiative, (3) organizational culture and structure (4) appropriation of innovation and (5) contribution / results.